Rancang Bangun Sistem Pengaman dan Monitoring Kendaraan Bermotor - Hoti Atabia; Syafaruddin Ch; Budi Darmawan; Paniran (Depertment of Electrical Engineering University of Mataram, 2023)
Motorcycle security is still manual and without double safety. One solution is to install guards and trackers on motorcycles. In designing this system using Arduino uno as a controller, SIM800L GSM module as a communication medium via SMS and the U-Blox Neo 6MV2 GPS Module. When a motorcycle is stolen, the security system in the form of an alarm will sound and provide a notification of theft warning in the form of an SMS to the user. This tool can also turn off motorbikes remotely and is equipped with a motorcycle location tracking system via Google Maps. The results of testing the motorcycle tracking system obtained that the average response time of the system providing a reciprocal SMS link location when the user requests the location of the motorcycle is 19.55 seconds. Then the average error distance difference between the position of the actual coordinate point on Google Maps and the position of the coordinate point measured on GPS is 2.111602 meters.